Sustainable intensification and carbon sequestration research in agricultural systems: A systematic review. Issue 143 (May 2023) - Haughey, E.; Neogi, S.; Portugal-Pereira, J.; van Diemen, R.; Slade, R.B.
Abstract: Mitigation pathways that stabilise global warming to 1.5 °C describe rapidly increasing deployment of land-based solutions, including increased carbon sequestration in soils and biomass. This places additional demands on land, which is also required to provide food security and other ecosystem services. Sustainable Intensification (SI) of agriculture has the potential to facilitate meeting demands for food and fibre, while simultaneously meeting environmental and ecological goals. The scientific literature has most often addressed the challenge of SI separately to climate change mitigation objectives in agricultural systems. Using a systematic review approach, we explored the compatibility of SI and carbon sequestration research through two contrasting case studies: Case Study I on Grassland Agriculture in Europe, and Case Study II on Smallholder Agriculture in Africa. We find contrasting levels of research theme similarity for SI and carbon sequestration, with European grassland agriculture research having lower similarity compared with African smallholder agriculture research. There was a focus on minimising biodiversity loss and environmental impacts in Europe, in contrast to a food security emphasis in Africa, reflecting regional and development differences. While there are clear context and agricultural-system specific differences between both case studies, both suggest that sustainable land use policies can be used to achieve SI integrated with climate mitigation in agriculture. Highlights: Climate mitigation pathways increasingly incorporate land-based carbon storage. Sustainable intensification (SI) of agriculture may reduce demand for land. We investigated the compatibility of research on SI and carbon sequestration. There were significant contrasts reflecting a need for better integration. Sustainable land use policies can help achieve mitigation where integrated with SI.